2020
DOI: 10.1086/710570
|View full text |Cite
|
Sign up to set email alerts
|

Detection of 4 imperiled western North American freshwater mussel species from environmental DNA with multiplex qPCR assays

Abstract: We developed multiplexed, species-specific, quantitative PCR assays for the detection of four freshwater mussel species native to western North America, Gonidea angulata, Margaritifera falcata, Anodonta nuttalliana and Anodonta oregonensis, from environmental DNA (eDNA). These species have experienced dramatic declines over the last century and are currently threatened in many portions of their ranges. Therefore, improved tools for detecting and monitoring these species are needed. Speciesspecificity and sensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Additionally, no recently deceased shells were observed at any site visited in 2014, and eDNA samples collected in 2022 downstream from 2 previously occupied sites tested negative for pearlshell DNA. Environmental DNA (eDNA) analysis has proven to be a useful and efficient tool for detecting rare aquatic organisms that are present but difficult to detect using traditional sampling surveys (Davy et al 2015, Dysthe et al 2018, Preece et al 2019, Rogers et al 2020). But in this case, it appears that eDNA has validated the absence of western pearlshell mussels in previously occupied areas.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, no recently deceased shells were observed at any site visited in 2014, and eDNA samples collected in 2022 downstream from 2 previously occupied sites tested negative for pearlshell DNA. Environmental DNA (eDNA) analysis has proven to be a useful and efficient tool for detecting rare aquatic organisms that are present but difficult to detect using traditional sampling surveys (Davy et al 2015, Dysthe et al 2018, Preece et al 2019, Rogers et al 2020). But in this case, it appears that eDNA has validated the absence of western pearlshell mussels in previously occupied areas.…”
Section: Discussionmentioning
confidence: 99%
“…This study identified a subset of coastal watersheds in which mussels were not observed in 1st-3rd order streams during the eleven year AQI survey period (SM, Figure S1). Environmental DNA (eDNA) monitoring technology has evolved as an effective monitoring tool to assess presence/absence of aquatic species in watersheds, and recent applications incorporate freshwater mussels assays (Rodgers et al, 2020;Preece et al, 2021). Identified watersheds should be prioritized for future monitoring to determine the status of mussel presence and/or extirpation in coastal watersheds to guide future efforts in population dynamics and extinction debt research in functionally isolated populations.…”
Section: Study Limitations/research Directionsmentioning
confidence: 99%
“…This is not surprising since freshwater ecosystems are considered the most imperilled habitats in the world (Reid et al, 2019), and at least in temperate regions they have been subject of intensive monitoring due to legal requirements, as already above-mentioned. In these ecosystems, most studies have been conducted in rivers and small streams (Castañeda et al, 2020;Ma et al, 2016;Mizumoto et al, 2020;Piggott, 2017;Riaz et al, 2020;Rodgers et al, 2020), lentic ponds (Adams et al, 2019;Geerts et al, 2018;Harper et al, 2018b) and lakes (Johansson et al, 2020;Kamoroff and Goldberg, 2018), to a small extent in reservoirs and dams (Nakao et al, 2023;Sepulveda et al, 2022Sepulveda et al, , 2019, channels (Beauclerc et al, 2019;, caves and springs (DiStefano et al, 2020;Vörös et al, 2017) and aquacultures (Deutschmann et al, 2019;Ladell et al, 2019) (Table S2).…”
Section: Edna-based Targeted Detection Of Rare Animal Species Has Bee...mentioning
confidence: 99%
“…Multiplex approaches have been less adopted but can be more cost-effective than DNA metabarcoding when the target is a few a priori well-known species (Jo et al, 2020;King et al, 2022;Robinson et al, 2018bRobinson et al, , 2018aRodgers et al, 2020;Tsuji et al, 2018;Wozney and Wilson, 2017) (Table S2). The use of multiplex designs can allow the simultaneous detection of numerous species, reducing processing and handling times, as well as the risk of contamination, lowering costs and reducing the amount of DNA extract required for testing (Rodgers et al, 2020;Wozney and Wilson, 2017). For instance, Robinson and co-authors (Robinson et al, 2018a) developed a multiplex assay for the simultaneous detection of the invasive signal (which was not certified by peer review) is the author/funder.…”
Section: 4mentioning
confidence: 99%